Exposure of Reference and Sense in English Textbook of Elementary Students of Grade One - Berlin Sibarani (Journal of Language, Literature and Teaching, 2021)
The objectives of this study were to describe the exposure of references in Elementary English textbooks. This study revealed that 96% in the attempt to teach the students the reference as the semantic properties of the objects. No systematic and organized attempts to expose the references which enable the students to develop their mental image critically and systematically. Exposure of senses is also found in the textbook although their occurrences are very few and limited in terms of number (4%) and types of sense. The sense exposed in the textbook is limited to attributes of various objects having the same expression and proper names. Systematic and purposeful organizations of this exposure are not found either. This might be caused by the lack of knowledge of the textbook writer about the semantic properties of objects (nouns), their relationship with the mental image development of the students. For better exposure of meanings of objects (nouns) in English textbooks, theories of reference and sense and other semantic properties of meaning must be taken into account. Keywords: reference, sense, elementary, mental image, textbook